Effects of resilience training for mothers on maternal resilience and children’s pain in pediatric burn units in a randomized controlled trial - Fahimeh Alsadat Hosseini; Maryam Shaygan; Maryam Shayegan (Scientific Reports)
Abstract Mothers of children with burn injuries often experience psychological distress, affecting their well-being and children’s pain. This study evaluates the impact of resilience training on maternal resilience and child pain. This randomized clinical trial was conducted at Amir Al-Momenin Burn Hospital, Shiraz, Iran, with 50 mothers in 2021–2022. Participants were assigned to an intervention group (six-day resilience training) or a control group (standard care). Outcomes were measured at multiple time points using the Connor-Davidson Resilience Scale and the Visual Analog Scale. Data were analyzed using SPSS v.22. The analysis revealed significant time effects on child pain intensity (B = − 0.84, p < 0.001) and maternal resilience (B = 3.99, p < 0.001). Significant group effects revealed greater improvements in the intervention group for child pain intensity (B = 2.85, p < 0.001) and maternal resilience (B = − 3.05, p < 0.001). The intervention group showed significant improvement in maternal resilience over time compared to the control group (B= − 2.06, p = 0.001), with no significant difference in child pain intensity over time compared to the control group (B = − 0.05, p = 0.69). Resilience training enhances maternal resilience and children’s pain over time. However, its impact on child pain intensity is limited compared to standard care. Therefore, integrating resilience training for mothers into pediatric burn care is recommended.